Batik Lasem motifs dataset: Gunung Ringgit, Kricak, Latohan, Nyuk Pitu, SeritanMendeley Data - Vera Jenny Basiroen; Ida Bagus Kerthyayana Manuaba (Data in Brief)
This dataset comprises five traditional Batik Lasem motifs: Gunung Ringgit, Kricak, Latohan, Nyuk Pitu, and Seritan. Batik Lasem, originating from Central Java, Indonesia, is renowned for its intricate patterns and vibrant red hue, known as getih pitik. These motifs represent a fusion of Javanese and Chinese artistic influences. Each motif was cropped from high-resolution photographs of authentic batik linens and is accompanied by metadata describing their historical and cultural significance. Researchers and designers can utilize these data for comparative studies, digital restoration, and contemporary design adaptations. The dataset is openly available in Mendeley Data to facilitate interdisciplinary studies on traditional textiles, cultural heritage preservation and digital applications in design and humanities.